2019
DOI: 10.1371/journal.pone.0221301
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral PD-1+CD56+ T-cell frequencies correlate with outcome in stage IV melanoma under PD-1 blockade

Abstract: Immune checkpoint blockade with anti-PD-1 antibodies is showing great promise for patients with metastatic melanoma and other malignancies, but despite good responses by some patients who achieve partial or complete regression, many others still do not respond. Here, we sought peripheral blood T-cell biomarker candidates predicting treatment outcome in 75 stage IV melanoma patients treated with anti-PD-1 antibodies. We investigated associations with clinical response, progression-free survival (PFS) and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…In melanoma patients, the peripheral TCR repertoire correlated with responses to checkpoint inhibitors [42][43][44], and similar results were reported for pancreatic ductal adenocarcinoma and other solid tumors [41]. Similarly, the evaluation of peripheral TCR repertoire of PD-1 + CD8+ lymphocytes also showed promising results as a non-invasive approach for selecting metastatic Melanoma TCR repertoire profiling is associated with immunotherapy response [42][43][44] Baseline frequency of CD14 + CD16-HLA-DRhi monocytes, CD69 + MIP-1β + NK cells, and PD-1 + CD56+ T cells are potential predictors of clinical response in patients treated with immunotherapy [45][46][47] The increase of central memory CD4+ T cells and the decrease of dysfunctional PD-1 + CD38hi CD8+ cells during immunotherapy are correlated with response. [48,49] Levels of circulating CD33 + CD11b + HLA-DR-myeloid derived suppressor and distinct CD4+ and CD8+ memory T cell subsets are correlated with survival of immunotherapy treated patients.…”
Section: Tcr Profiling Of Lymphocytes From Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma patients, the peripheral TCR repertoire correlated with responses to checkpoint inhibitors [42][43][44], and similar results were reported for pancreatic ductal adenocarcinoma and other solid tumors [41]. Similarly, the evaluation of peripheral TCR repertoire of PD-1 + CD8+ lymphocytes also showed promising results as a non-invasive approach for selecting metastatic Melanoma TCR repertoire profiling is associated with immunotherapy response [42][43][44] Baseline frequency of CD14 + CD16-HLA-DRhi monocytes, CD69 + MIP-1β + NK cells, and PD-1 + CD56+ T cells are potential predictors of clinical response in patients treated with immunotherapy [45][46][47] The increase of central memory CD4+ T cells and the decrease of dysfunctional PD-1 + CD38hi CD8+ cells during immunotherapy are correlated with response. [48,49] Levels of circulating CD33 + CD11b + HLA-DR-myeloid derived suppressor and distinct CD4+ and CD8+ memory T cell subsets are correlated with survival of immunotherapy treated patients.…”
Section: Tcr Profiling Of Lymphocytes From Cancer Patientsmentioning
confidence: 99%
“…The predictive role of specific leukocyte subsets in patients undergoing anti-PD-1 and anti-CTLA4 immunotherapy has been investigated mostly in metastatic melanoma and lung cancer patients. The baseline frequency of CD14 + CD16-HLA-DRhi monocytes [45], CD69 + MIP-1β + NK cells [46], and PD-1 + CD56+ T cells [47] were reported to be predictors of clinical response in metastatic melanoma patients treated with anti-PD-1 immunotherapy. In the same setting, the post-treatment increase of the specific subset of central memory CD4+ T cells, harboring the CD27 + FAS-CD45RA-CCR7+ phenotype, was associated to prolonged clinical responses [48].…”
Section: Immunoprofiling Of Peripheral Leukocytes From Cancer Patientsmentioning
confidence: 99%
“… 32 Tumor immunogenicity scores are under evaluation as predictors for responses to ICI. 33 Previous studies already indicated peripheral blood immune cell subsets like PD-1 + CD56 + T cells 34 or CD4+ and CD8+ cells 35 to be associated with favorable outcome for advanced melanoma patients treated with ipilimumab directed against cytotoxic T lymphocyte antigen-4 (CTLA-4). Now we identified a liquid immune profile-based signature to predict response of patients with metastatic cancer to anti-PD-1/PD-L1 treatment at an early time point.…”
Section: Discussionmentioning
confidence: 99%
“…32 Tumor immunogenicity scores are under evaluation as predictors for responses to ICI. 33 Previous studies already indicated peripheral blood immune cell subsets like PD-1 + CD56 + T cells 34 or CD4+ and CD8+ cells 35 to be associated with favourable outcome for advanced melanoma patients treated with ipilimumab directed against cytotoxic T lymphocyte antigen-4 (CTLA-4). Now we identified a liquid immune profile-based signature to early predict response of metastatic cancer patients to anti-PD-1/PD-L1 treatment.…”
Section: Discussionmentioning
confidence: 99%